Histo-Epidemiological Profile of Digestive Cancers in Togo (Journal of Cancer Research Updates, 2015)
Background:The frequency of digestive cancers is increasing since the last ten years. The aim of the study was to determine the epidemiologic and histologic aspects of digestive cancers in Togo. Method: We conducted a descriptive cross-sectional study focused on digestive cancers cases diagnosed from 1995 throughout 2014 (20 years) at the pathology laboratory of the Lomé teaching hospital. We included all digestive samples (biopsy, excision, surgical specimens) collected and sent to the pathology laboratory from 1994 to 2013 using data from the records of the laboratory. Results: We have collected 1306 cases of digestive cancers (20.4%). The annual incidence was 65.3 cases. The sex-ratio (M/F) was 1.5. The mean age was 47.8 years. The most common locations were the stomach (35.3%) and the esophagus (27.3%). The adenocarcinoma was predominant in the stomach (84.4%), the rectum (70.2%), and the colon (86.3%). The squamous cell carcinoma was commonly found at the esophagus (94.8%). The lymphomas were observed in the small intestine (53.4%). Conclusion: Digestive cancers are frequent in Togo and occur in young adults. The stomach cancer is the most common cancer